UPAYA PATROLI SATSAMAPTA DALAM PENCEGAHAN TINDAK PIDANA CURAT GUNA MEWUJUDKAN KAMTIBMAS DI WILAYAH HUKUM POLRES PATI - Multahadi Adam Adam (Police Studies Review, 2022)
ABSTRACT THE EFFORTS OF SAMAPTA UNIT PATROL IN PREVENTING CRIME OF STEALING TO CREATE KAMTIBMAS IN THE JURISDICTION OF THE PATI POLICE Multahadi Adam, 18.030, multahadiadam1@gmail.com This research is based by the high number of cases of theft with weights that have been special attention and become one of the highest crimes that occur in the jurisdiction of the Pati Police. The Police need to take preventive action, one of them is patrol to prevent the meeting of intentions and opportunities from criminals, especially in theft by weight. Therefore, the purpose of this study is to describe the efforts of the Samapta unit and what factors affect the implementation of patrols and efforts to maintain security and social order in patrols that carried out by the Pati Police Satsamapta. This type of research uses field research and a qualitative approach. Sources of data include primary data and secondary data with data collection techniques used are interviews, observations, document studies, and focus group discussions. Data analysis techniques that used were include data reduction, data presentation and drawing conclusions. The analytical knife in conducting the discussion includes POAC management theory and Routine Activity theory, as well as to look for influencing factors using SWOT theory. The results of the study found that the crime of stealing is still a special attention at the Pati Police. The activities carried out by the Pati Police Samapta Unit were not carried out according to the SOP, namely the termination stage which was not carried out optimally. Judging from several factors, there are internal and external factors. The most influential internal factor is the lack of vocational education carried out by patrol members and externally, namely the high number of cases of the spread of the Covid-19 virus, which causes the focus of the patrol to be divided. Efforts have been made to establish the Pasopati Timsus to optimize the implementation of the Pati Police Satsamapta patrol. However, the implementation found obstacles, namely the unclear division of tasks, causing the focus to be fragmented. Based on the results of the study, the authors suggest that when making patrol routes always pay attention to the budget and the latest crime-prone areas. In order to establish cooperation with the Polsek, the community and other Pam Swakarsa, such as kamling posts and security posts. As well as to add CCTV and street lighting in areas prone to criminal acts of stealing.